Exploring the Mechanism of the Baishao Luoshi Formula against Poststroke Spasticity by Network Pharmacology and Experimental Validation - Zeng, Shanshan; Xie, Le; Mao, Guo; Xie, Yao; Cao, Sijia; Liu, Dong; Wu, Dahua (Current Computer - Aided Drug Design, 2022)
Background: Post-stroke spasticity (PSS) is a major cause of disability, leading to severely impaired upper-limb flexibility and ability to walk and move, significantly affecting the quality of life of cerebral infarction patients. There is currently no recognized effective therapy. Alternatively, Chinese traditional medicine has shown promise for PSS treatment. In this regard, the BSLSF has been reported to be effective; however, its underlying mechanism remains unclear. Objective: The objective of this study is to clarify the main targets and pathways of Baishao Luoshi Formula (BSLSF) during PSS treatment, laying the foundation for further research on its pharmacological effects. Methods: In this study, network pharmacology and experimental verification were conducted to explore the potential mechanism of BSLSF systematically. After obtaining active ingredients of BSLSF from the TCMSP database, SwissTarget-Prediction and PharMapper were used to uncover BSLSF targets. PSS-related targets were gathered with GeneCards and Online Mendelian Inheritance in Man. The differentially expressed genes between BSLSF and PSS were identified by a Venn plot. The drugactive ingredient-target interaction network and Protein-protein interaction (PPI) were constructed using Cytoscape and further analyzed using the MCC algorithm of CytoHubba plugin. Then, Pathway enrichment and GO biological process enrichment analyses were performed. Subsequently, a mice model of middle cerebral artery occlusion (MCAO) was established for the in vivo experiments. Results: We found that AKT1, TNF, CASP3, VEGFA, and CREB1 were potential targets during PSS treatment. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses showed that the mechanism of PSS was closely related to synaptic plasticity. And the immunohistochemical staining showed that BSLSF protected against ischemic stroke via the CCR5/CREB signaling pathway and probably affected synaptic plasticity. Conclusion: our study validated that treatment with BSLSF protected against ischemic stroke via the CCR5/CREB signaling pathway and could affect synaptic plasticity. In a sense, this study provides the basis for further extensive and in-depth analysis of BSLSF, enabling the quest for new drug targets at the same time.
Keywords: CCR5